2023
DOI: 10.1002/cbin.12003
|View full text |Cite
|
Sign up to set email alerts
|

ARID3A plays a key regulatory role in palmitic acid‐stimulated milk fat synthesis in mouse mammary epithelial cells

Abstract: Palmitic acid (PA) can stimulate milk fat synthesis in mammary gland, but the specific mechanism is still unclear. In our research, we aim to explore the role and corresponding mechanism of AT‐rich interaction domain 3A (ARID3A) in milk fat synthesis stimulated by PA. We found that ARID3A protein level in mouse mammary gland tissues during lactation was much higher than that during puberty and involution. ARID3A knockdown and gene activation showed that ARID3A stimulated the synthesis of triglycerides and chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…9 As far as we know, a few reports have also shown that protein members in SWI/ SNF, a main chromatin remodeling complex, can respond to extracellular nutrient signals to regulate milk synthesis in MECs. For examples, ARID1B plays an inhibitory role in Met stimulation on mTOR transcriptional activation and milk synthesis in MECs 10 ; ARID3A mediates palmitic acid stimulation on mTOR mRNA expression and milk lipid synthesis in MECs 28 ; and BRM, as a positive regulator, participates in proliferation of MECs and mediates Leu induction on mTOR transcriptional activation and protein phosphorylation. 11 In this study, we further uncover that BRCC36 is a negative regulator of BRG1 protein level, mTOR mRNA level, and protein phosphorylation.…”
Section: ■ Discussionmentioning
confidence: 99%
“…9 As far as we know, a few reports have also shown that protein members in SWI/ SNF, a main chromatin remodeling complex, can respond to extracellular nutrient signals to regulate milk synthesis in MECs. For examples, ARID1B plays an inhibitory role in Met stimulation on mTOR transcriptional activation and milk synthesis in MECs 10 ; ARID3A mediates palmitic acid stimulation on mTOR mRNA expression and milk lipid synthesis in MECs 28 ; and BRM, as a positive regulator, participates in proliferation of MECs and mediates Leu induction on mTOR transcriptional activation and protein phosphorylation. 11 In this study, we further uncover that BRCC36 is a negative regulator of BRG1 protein level, mTOR mRNA level, and protein phosphorylation.…”
Section: ■ Discussionmentioning
confidence: 99%
“…It is yet unknown how GPR110 can stimulate mTOR phosphorylation and SREBP-1c expression. We have previously shown that PA can stimulate mTOR phosphorylation and SREBP-1c expression through activating PI3K (46,47) , which is often a downstream signalling molecular of many GPCR such as GPCR6A (8,47) . We thus speculate that GPR110 can stimulate mTOR phosphorylation through the PI3K signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Consolidating our target mRNA predictions from TargetScan and miRDB platforms established a list of 192 putative mmu-let-7b-5p mRNA targets showing increased abundance during infection, including Integrin Beta 3 subunit (Itgb3, Log2 FC = 2.35), Argonaute RISC Catalytic Component 2 (Ago2, Log2 FC = 1.37), Dual-specificity phosphatase 9 (Dusp9, Log2 FC = 1.94) (Figure2A) and 7 mRNAs encoding for transcription factors (TFs) or epigenetic regulators (ERs), i.e. Arid3a, E2f6, Hmga1, Klf8, Nr6a1, Pbx1, and Zfp202 (Figure2B), which are involved in regulation of proliferation regulation, cell differentiation, DNA structure modification, and cancer-related signaling pathways(Trimarchi et al 2001, Patterson et al 2008, Wang et al 2022, Guo et al 2023, Bai et al 2024, Kao et al 2024, Zhang et al 2024.…”
mentioning
confidence: 99%